Excess of zinc reduces the growth of bulb onion plants (Allium cepa L.) - Casierra-Posada, Fánor; Trujillo-Niño, Luis Miguel (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2024)
While zinc (Zn) is an essential element for plant metabolism, anthropic activities and poor agricultural practices as well as frequent use of pesticides and fertilizers rich in this element can cause toxic levels of Zn to plants. A study was done under greenhouse conditions in Tunja, Colombia in which bulb onion seedlings (Allium cepa L.) were exposed to 0 (control), 20, 40, and 80 mg L-1 of Zn in mixture with a nutrient solution containing macro and micronutrients. The excess Zn in the solution had a rather drastic effect on the accumulation of dry weight and reduced the absolute growth rate, the specific leaf area, the water uptake, the water use efficiency, the leaf area, the length of all roots per plant, and on the contrary, increased the content of total soluble solids in the juice of the bulb. Thus, most growth-related variables were negatively affected from 20 mg L-1 and up of Zn in solution. In addition, the toxic effect of Zn is more drastic on plants growing in nutrient solution compared to those growing in soil. The experiment lasted until 54 days after transplanting, which was the limit for plant survival, especially at higher concentrations of Zn, so it can be inferred that these plants have low tolerance to high Zn contents in the substrate.